The Experiences of Younger Individuals Living With Heart Failure. Issue 6 (November 2018) - Walsh, Alison; Kitko, Lisa; Hupcey, Judith
Abstract : Background: Heart failure (HF) impacts 1.7 million Americans between the ages of 20 and 59 years, but limited research exists addressing the issues unique to this age group. Objective: The aim of this study was to investigate the experiences of younger persons living with HF. Methods: Semistructured interviews (n = 18) were analyzed using a qualitative thematic analysis. Results: Six themes emerged: (1) role fulfillment: participants who perceived their roles as a parent, caregiver, spouse, employee, and friend have been negatively affected by HF; (2) autonomy: participants frequently linked their well-being to a sense of independence, productivity, and purpose; (3) financial impact: most of the sample expressed financial instability further complicated by existing disability policies; (4) perception of self: recurrent statements revealed participants feeling judged because of their HF diagnosis and younger age; (5) retrospective life changes: participants reflected on past decisions and often blamed themselves for their current health; and (6) symptom burden: participants reported higher levels of psychosocial symptoms, such as depression, anxiety, and fatigue. Conclusions: Younger individuals living with HF reported overwhelmingly poor health-related quality of life that was linked to the 6 themes identified previously. The effect of HF was seen on numerous life events that traditionally occur earlier in the life course such as establishing a career, meaningful relationships, family, and financial security. This directly impacted health-related quality of life by disrupting what each individual perceived as important to them, which took a toll on their overall mental health. To provide holistic care to younger patients living with HF, interventions that address the heavy burden of psychosocial symptoms and policy changes associated with financial burden and disability laws must be developed.